Income and wealth inequality in Malta: evidence from micro data - Ilias Georgakopoulos (Central Bank of Malta, 2019)
This paper studies the distribution of income and wealth in Malta over the period 2010-16, based on three waves of detailed micro-data from the Household Finance and Consumption Survey. This is the first paper that explores the evolution of income and wealth inequality jointly, and over time, using household-level data in Malta. In particular, the focus of the present paper is to examine how income and wealth are distributed over different socioeconomic characteristics, their joint distribution and its determinants, as well as factors that influence a household's ability to obtain credit, using decomposition methods and binary response models. Our results suggest that households with tertiary education experienced strong increases in their incomes and wealth in the period examined. With reference to wealth, household main residence (HMR) is the most equalising factor of wealth inequality and self-employment wealth is the most disequalising factor. Regarding the determining factors of the position of a household in the wealth distribution, the financing structure of HMR is particularly important to explain the household's position in the wealth distribution. Furthermore, the age and education level of the reference person of a household as well as increases in household's income affect positively the probability of being in a higher wealth quintile. This finding also holds true for households who have received inheritance or gifts.
Keywords: D31; C35; D10; D63; D39; 330